Stem cells and healthy aging - Goodell, Margaret A; Rando, Thomas A (Science (American Association for the Advancement of Science), 2015)
Research into stem cells and aging aims to understand how stem cells maintain tissue health, what mechanisms ultimately lead to decline in stem cell function with age, and how the regenerative capacity of somatic stem cells can be enhanced to promote healthy aging. Here, we explore the effects of aging on stem cells in different tissues. Recent research has focused on the ways that genetic mutations, epigenetic changes, and the extrinsic environmental milieu influence stem cell functionality over time. We describe each of these three factors, the ways in which they interact, and how these interactions decrease stem cell health over time. We are optimistic that a better understanding of these changes will uncover potential strategies to enhance stem cell function and increase tissue resiliency into old age.